Relationship Between Dryland Profile and Kinematics of Breaststroke Pullout Techniques - Costa, Mário J.; Gay, Ana; Ferreira, Francisco A.; Vilas Boas, Joao Paulo; Santos, Catarina C. (International Journal of Sports Medicine, 2025)
The aim of this study was twofold: (1) to make a sex comparison on dryland strength, range of motion (ROM), and kinematics of the breaststroke underwater pullout and (2) to analyze the relationship between dryland strength, ROM, and kinematics of different pullout techniques in both male and female swimmers. Sixteen trained swimmers, nine males (20.67±2.71 years old) and seven females (18.86±0.83 years old), performed 3×25 m breaststroke using two pullout breaststroke techniques: Fly-Kick first and Combined. A speedometer and video footage were used to assess the pullout phase kinematics and the total underwater sequence. Dryland assessments included the maximum jump height, the isometric peak strength of internal shoulder rotation (IR) (at 90°), and knee extensors (at 60°). The joint ROM of knee flexion (KF), plantar flexion (PF), and hip internal rotation were also considered. Velocity–time curves of both techniques according to sex were dissected using statistical parametric mapping. An independent t-test was used to compare differences between swimmers’ sex in kinematic and dryland variables while the Pearson correlation coefficient (r) was used for associations. Higher instantaneous velocity at ~24–26, ~31–42, and 54.5–63% during the glide phase duration was found for males in the Fly-Kick first technique. Males also displayed a higher peak (3.29 m·s−1) and mean velocity (1.58–1.65 m·s−1) in the total underwater path or in the glide and propulsion phases of both pullout techniques. While males performed better in jump height (33.89 cm) and peak strength of IR (172–176 N), females showed a higher ROM mostly in PF (161–165°). A high and positive correlation between dryland strength and kinematics in both pullout techniques was found in males. The ROM failed to correlate with pullout kinematics, except for the KF in females during the recovery phase (r=0.82–0.86). In conclusion, male breaststrokers perform better than females on dryland strength but not in joint ROM, which provides them with an advantage mainly in the Fly-Kick first underwater pullout.
Keywords: swimming; training; biomechanics; underwater pullout